Research Reconfiguration Method for Warship Power System Based on Graph Trace Analysis and Generic Algorithms - Xia, Li; Shang, An Li; Wang, Zheng (Applied Mechanics and Materials, 2014)
The electric power network reconfiguration of warship integrated power system is one of the most important methods to restore power supply and improve survivability of shipboards under fault. The reconfiguration method based on graph trace analysis (GTA) and generic algorithms is proposed for warship integrated power system in order to maximize the number of served loads with highest priority under fault. Simulation results have demonstrated that is method is able to reach target configurations.